Food Waste: Addressing our 160 Billion Pound Public Health Challenge with Policy and Business Interventions - Swinburne, Mathew; Sandson, Katie (Journal of Law, Medicine & Ethics, 2019)
The United States wastes approximately 40% of its food supply. This article will examine the implications of this waste for food insecurity and climate change. It will also explore how the law and social entrepreneurship can be used to confront this public health challenge.
Keywords: Réservé UdeM; États-Unis